Early Christian Basilicas in Crimea and their Numeric Proportions - Buchwald, H.; Zavadskaya, I. (Материалы по археологии, истории и этнографии Таврии, 2013)
The focus of this study is to determine the extent to which numeric (as opposed to geometric) proportions were employed in Christian basilicas of Crimea and which specific numeric proportions were applied; it also attempts to explain why certain proportions may have been chosen by the builders. Numeric proportions were identified in 14 basilicas of Crimea: 10 in Chersonesos, two on the plateaus of Mangup-Kale and Eski-Kermen in southwest Crimea, one in Partenit on the south coast and one in Tyritake, south of modern Kerch at the east end of Crimea. Most reviewed basilicas have reasonably been attributed to the 6th and early 7th centuries based largely upon archaeological evidence.